2022
DOI: 10.1556/004.2022.00029
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and its impact on environmental survival and antibiotic resistance of Mycoplasma anserisalpingitidis strains

Abstract: Several Mycoplasma species can form biofilm, facilitating their survival in the environment, and shielding them from therapeutic agents. The aim of this study was to examine the biofilm-forming ability and its potential effects on environmental survival and antibiotic resistance in Mycoplasma anserisalpingitidis, the clinically and economically most important waterfowl Mycoplasma species. The biofilm-forming ability of 32 M. anserisalpingitidis strains was examined by crystal violet assay. Biofilms and plankto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Biofilm formation contributes to the persistence of Mycoplasma anserisalpingitidis in the environments from which the isolates were obtained. Antibiotic susceptibility was not affected by biofilm formation; however, it is important to highlight that the correlation was only evaluated in vitro [6].…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm formation contributes to the persistence of Mycoplasma anserisalpingitidis in the environments from which the isolates were obtained. Antibiotic susceptibility was not affected by biofilm formation; however, it is important to highlight that the correlation was only evaluated in vitro [6].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the absence of cell walls and defense mechanisms, mycoplasma typically has a limited lifespan in the external environment ( Justice-Allen et al, 2010 ). The formation of biofilms helps mycoplasma survive in the environment outside of its host ( Beko et al, 2022 ). Thus far, only a limited number of studies have demonstrated the ability of certain Mycoplasma gallisepticum strains to develop biofilms, and subsequent investigations in this area are needed ( Perez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beside their capability to inhibit the expulsion of most of the clinically important antibiotics from the intracellular environment, there are recent publications about their role in the inhibition of biofilm formation by interfering in the process of releasing the quorum sensing molecules by efflux pumps which facilitate biofilm matrix formation (AlMatar et al, 2021). Based on previous studies (Bekő et al, 2022), biofilm formation can assist M. anserisalpingitidis to survive in the environment. Considering the observed effects of the EPI CCCP against M. anserisalpingitidis in the present study, and the probable interference with biofilm formation, it is assumed, that the use of EPIs would increase the efficiency of targeted antibiotic therapy in the control of this pathogen.…”
Section: Discussionmentioning
confidence: 99%